Evaluation of Antibiotic Appropriateness Assessed by Changes in C-Reactive Protein (CRP) Levels in Patients with Deep Neck Abscesses - Mohammad Dwijo Murdiyo; I Made Indra Wijaya (Journal of Medical Practice and Research, 2026)
Deep neck abscesses are potentially life-threatening infections requiring prompt surgical drainage and appropriate antimicrobial therapy. This retrospective analytic study evaluated antibiotic appropriateness using early changes in C-reactive protein (CRP) levels as a biomarker of therapeutic response. From 38 eligible cases, 19 patients with confirmed bacterial isolates and documented antibiotic sensitivity results were included. Patients were stratified according to concordance between empirical antibiotics and culture sensitivity findings. Gram-positive organisms predominated (68.42%), with Streptococcus anginosus identified most frequently (36.84%). In the culture-concordant group, mean CRP decreased from 23.10 mg/L to 10.13 mg/L within 72 hours (mean reduction 12.97 mg/L; p=0.001), exceeding the minimal clinically important difference (2.85 mg/L). In contrast, the discordant group demonstrated a non-significant reduction from 14.10 mg/L to 9.43 mg/L (mean reduction 4.67 mg/L; p=0.206). These findings indicate that CRP kinetics provide quantifiable evidence of antibiotic appropriateness and may serve as an objective adjunct in guiding early antimicrobial stewardship in deep neck abscess management.